The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/la0484873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Iridium Oxide Thin Film on the Electrochemical Activity of Platinum Nanoparticles

Abstract: The influence of the iridium oxide thin film on the electrocatalytic properties of platinum nanoparticles was investigated using the electro-oxidation of methanol and CO as a probe. The presence of the IrO(2) thin film leads to the homogeneous dispersion of Pt nanoparticles. For comparison, polycrystalline platinum and Pt nanoparticles dispersed on a Ti substrate in the absence of an IrO(2) layer (Ti/Pt) were also investigated in this study. Inverted and enhanced CO bipolar peaks were observed using an in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 41 publications
7
84
0
Order By: Relevance
“…Even if there is no good correlation between the CO adsorption and electrochemically active surface area, there is a clear difference in the shape of the CO-stripping peak for Pt and PtIr. Chen et al showed in their study that the H UPD charges and the CO-stripping charges gave similar values for the electrochemically active surface area of electrodes with Pt deposited on Ir oxide, assuming linearly bonded CO [51]. However, for the 3Pt3Ir electrodes covered with Nafion used in this work, the H UPD charges are very low which is similar to observations made by Slavcheva et al where diminishing H UPD charges on sputtered electrodes with Pt and Ir oxide with increasing hydration of the Ir oxide layer was seen [29].…”
Section: Electrochemical Resultsmentioning
confidence: 86%
“…Even if there is no good correlation between the CO adsorption and electrochemically active surface area, there is a clear difference in the shape of the CO-stripping peak for Pt and PtIr. Chen et al showed in their study that the H UPD charges and the CO-stripping charges gave similar values for the electrochemically active surface area of electrodes with Pt deposited on Ir oxide, assuming linearly bonded CO [51]. However, for the 3Pt3Ir electrodes covered with Nafion used in this work, the H UPD charges are very low which is similar to observations made by Slavcheva et al where diminishing H UPD charges on sputtered electrodes with Pt and Ir oxide with increasing hydration of the Ir oxide layer was seen [29].…”
Section: Electrochemical Resultsmentioning
confidence: 86%
“…Electrochemical impedance spectroscopy has been a powerful and sensitive technique to study electrochemical kinetics, for instance, in the investigations of the electro-oxidation process of small organic molecules in fuel cells. [45][46][47][48] From the voltammetric studies presented above, it can be seen that the loading of the FePt nanoparticle catalysts strongly affects the electrochemical reaction dynamics of formic acid oxidation, which were further examined by EIS measurements, as presented below. Figure 5 shows the Nyquist complex-plane impedance spectra of the electrodes with one, two, and four FePt particle layers in 0.1 M HCOOH and 0.1 M HClO 4 at varied electrode potentials from -0.3 to +0.9 V (shown as figure legends).…”
Section: Electrochemistry Of Ptfe Functionalized Electrodesmentioning
confidence: 99%
“…The addition of IrO 2 to Pt-RuO 2 shifts ethanol oxidation to lower potentials. Chen et al [24] used IrO 2 to increase the methanol oxidation rate on PtIrO 2 /C. The IrRu carbon supported/unsupported (88%Ir12%Ru)/C anodes showed higher performance than PtRu/C in DMFC [25].…”
Section: Introductionmentioning
confidence: 99%